2019
DOI: 10.1186/s11689-019-9272-2
|View full text |Cite
|
Sign up to set email alerts
|

Children with facial paralysis due to Moebius syndrome exhibit reduced autonomic modulation during emotion processing

Abstract: Background Facial mimicry is crucial in the recognition of others’ emotional state. Thus, the observation of others’ facial expressions activates the same neural representation of that affective state in the observer, along with related autonomic and somatic responses. What happens, therefore, when someone cannot mimic others’ facial expressions? Methods We investigated whether psychophysiological emotional responses to others’ facial expressions were impaired in 13 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 101 publications
3
32
1
1
Order By: Relevance
“…PS abnormalities can be associated to another clinical entity, the Möbius syndrome, which is characterized by unilateral or bilateral congenital facial nerve paralysis with impairment of ocular abduction frequently associated with limb anomalies. 27 However, the cranial nerve examination in our patient did not find any facial nerve dysfunction.…”
Section: Discussioncontrasting
confidence: 56%
“…PS abnormalities can be associated to another clinical entity, the Möbius syndrome, which is characterized by unilateral or bilateral congenital facial nerve paralysis with impairment of ocular abduction frequently associated with limb anomalies. 27 However, the cranial nerve examination in our patient did not find any facial nerve dysfunction.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, adults with Moebius syndrome, a congenital form of facial paralysis, are able to recognize photographs of emotion expressions with the same accuracy as control participants (Bogart and Matsumoto, 2010). However, a recent study (De Stefani et al, 2019) revealed that, compared with a control group, children with Moebius syndrome were slightly less accurate in labeling videos of facial expressions and showed less pronounced responses of parasympathetic system during observation of social stimuli. In addition, although adults with acute facial palsy are able to accurately recognize facial expression, these judgments can take longer than in control participants (Storbeck et al, 2019).…”
Section: Embodied Simulation and Emotion Recognitionmentioning
confidence: 98%
“…The third line of evidence is strictly connected to the facial mimicry mechanism, demonstrating that both in case of blockage/alteration by means of various experimental manipulations (e.g. pens or chopsticks [Ponari, Conson, D'Amico, Grossi, & Trojano, 2012], mouthguards [Rychlowska et al, 2014], hardening gels , botulinum [Baumeister, Papa, & Foroni, 2016]) and in case of individuals suffering from congenital or acquired facial and expression production disorders, difficulties in recognizing facial expressions have been reported (Bate, Cook, Mole, & Cole, 2013;Calder, Keane, Cole, Campbell, & Young, 2000;Giannini et al, 1984;McKone & Robbins, 2011;Nicolini et al, 2019;De Stefani et al 2019). This whole body of evidence supports the notion that the simulation mechanism may optimally work when facial feedback is consistent with the internal simulation (Wolpert & Flanagan, 2001); thus, interfering with facial mimicry may cause an incongruent signal with the pattern of sensorimotor activity and would result in a drop of recognition/discrimination accuracy (Wingenbach, Brosnan, Pfaltz, Plichta, & Ashwin, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, we involved subjects with Moebius Syndrome (MBS) 1 , an extremely rare congenital non-progressive condition resulting in severe or complete bilateral facial paralysis, resulting in a selective alteration of facial mimicry. Given the rarity of the syndrome, only few studies have investigated emotion recognition in MBS subjects, and, further, they present inconsistent results (Bate et al, 2013;Calder et al, 2000;Giannini et al, 1984;Nicolini et al, 2019;De Stefani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation